2013
DOI: 10.1002/cssc.201300751
|View full text |Cite
|
Sign up to set email alerts
|

A Mesoporous Carbon‐Supported Pt Nanocatalyst for the Conversion of Lignocellulose to Sugar Alcohols

Abstract: The conversion of lignocellulose is a crucial topic in the renewable and sustainable chemical industry. However, cellulose from lignocellulose is not soluble in polar solvents, and is, therefore, difficult to convert into value-added chemicals. A strategy to overcome this drawback is the use of mesoporous carbon, which enhances the affinity between the cellulose and the catalyst through its abundant functional groups and large uniform pores. Herein, we report on the preparation of a Pt catalyst supported on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…The Pt‐loaded carbon catalyst exhibited a high 80% yield of hexitol from cellulose, the best performance reported thus far. This probably resulted from the open pore structure, which permitted cello‐oligomers to effectively diffuse to the active sites inside the pore . Stein's group fabricated hollow carbon spheres with mesoporous shells by nanocasting carbon into dendritic MSNs via phenol‐paraformaldehyde gas‐phase polymerization and subsequently removing the silica structure by hydrofluoric acid etching …”
Section: Applications Of Dendritic Silica Particles With Center‐radiamentioning
confidence: 99%
“…The Pt‐loaded carbon catalyst exhibited a high 80% yield of hexitol from cellulose, the best performance reported thus far. This probably resulted from the open pore structure, which permitted cello‐oligomers to effectively diffuse to the active sites inside the pore . Stein's group fabricated hollow carbon spheres with mesoporous shells by nanocasting carbon into dendritic MSNs via phenol‐paraformaldehyde gas‐phase polymerization and subsequently removing the silica structure by hydrofluoric acid etching …”
Section: Applications Of Dendritic Silica Particles With Center‐radiamentioning
confidence: 99%
“…Carbons are hydrothermally stable under the reaction conditions typically at temperatures of 423-573 K. Moreover, the surface of carbon materials can be furnished with plenty of OH and carboxyl groups. Such weak acidic sites have been found to contribute to the activation of the glycosidic bonds in cellulose and consequently promote the hydrolysis of cellulose [27,35,[47][48][49][50][51]. Conversely, strong acid sites on carbon materials are unequivocally effective for cellulose hydrolysis [52][53][54].…”
Section: Catalysts and Reaction Mechanismsmentioning
confidence: 99%
“…This yield was the highest obtained in this study. Moreover, the total ballmilling and reaction time (4.5 h) was remarkably shortened by this optimized process compared with previously published methods where the overall time was greater than 24 h (Park et al 2013). This result demonstrated that mixed ball-milling of cellulose and solid acid catalyst is highly effective in promoting cellulose conversion.…”
Section: Comparison Of Ball-milling Modesmentioning
confidence: 66%